2021
DOI: 10.1002/iid3.473
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of transitional regulatory B and regulatory T cells and immunosuppressive drug doses in stable renal transplant recipients

Abstract: Objectives Regulatory B cells (Bregs) and T cells (Tregs) are thought to be involved in the regulation of graft acceptance in renal transplant recipients. However, mechanisms that affect Breg differentiation and interaction with Tregs are rather unclear. Methods Using eight‐color‐fluorescence flow cytometry, Tregs and CD19+ CD24hiCD38hi Bregs were analyzed in whole blood samples of 80 stable kidney transplant recipients, 20 end‐stage renal disease (ESRD) patients and 32 healthy controls (HC). In addition, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…No correlation was found between the frequencies and absolute numbers of tBregs and Tregs in dialysis patients, either before or after transplantation. Ibrahim et al [ 24 ] and Piloni et al [ 29 ] reported similar results. However, it is important to note that Piloni’s study focused on lung transplantation and not on kidney transplantation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…No correlation was found between the frequencies and absolute numbers of tBregs and Tregs in dialysis patients, either before or after transplantation. Ibrahim et al [ 24 ] and Piloni et al [ 29 ] reported similar results. However, it is important to note that Piloni’s study focused on lung transplantation and not on kidney transplantation.…”
Section: Discussionsupporting
confidence: 55%
“…Our results are in contrast to those of Shabir et al [ 27 ], who found no association between tBregs frequency and eGFR 12 months after transplantation. However, Imrahim EH et al [ 24 ] found that only the frequency of tBregs was associated with the eGFR, although not significantly, but not the absolute number. We found a significant correlation between the eGFR and the frequency of plasmablasts, suggesting that only the frequency of plasmablasts and both the frequency and absolute number of tBregs are associated with renal function.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…29 Rebollo-Mesa et al, in the Genetic Analysis of Molecular Biomarkers of Immunologic Tolerance (GAMBIT) study, observed a slightly higher proportion of TrBs in patients receiving reduced or no corticosteroids, but this result was not fully explained by reduction of immunosuppression. 30 We have recently shown that higher TrB percentages were not associated with lower immunosuppression, 31 and already in our first analysis, we found that on day 135 after transplantation, before steroids were stopped in three of four group C patients, the median TrB percentage was already 9% (range 2%-20%), which was considerably higher than in transplanted controls. 6 In the current analysis, TrB percentages in MICtreated patients were 75-fold higher than TrB percentages in patients with minimal immunosuppression (LTS-mi) and seven-fold higher than TrB percentages in operationally tolerant patients without MIC treatment, clearly showing that the increase in TrBs cannot be explained by immunosuppression reduction alone.…”
Section: Discussionmentioning
confidence: 51%
“…This approach has also lead to novel insights in other solid organs transplants, such as kidney (2)(3)(4)(5), liver (6), heart (7), and lung transplantation (8,9). There have been several studies highlighting the relevance of subsets of T cells and B cells on the outcome of organ transplantation (4,5,10,11). This understanding of transplant immunology has led to the development of strategies to mitigate immunosuppression side effects, by identification of donorspecific B and T cells prior to transplantation and adjusting immunosuppression accordingly (12), or through the treatment with regulatory cell therapies (13).…”
Section: Introductionmentioning
confidence: 99%